NIKAH MISYAR (Analisis Maqashid asy-Syari’ah) - Syahrial Dedi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
The marriage misyar is a marriage contract conducted by husband and wife in syar'i and meet all the terms of marriage in islamic law. But the wife sincerely gave up her right not to be fulfilled by her husband, such as living in the house and the material right as usual of marriage. This marriage has been widely studied by Muslim intellectuals from various aspects such as, such as sociological, legal, and maqashid asy-syari'ah. Among the studies of the highlights maqashid ay-syari'ah concluded that marriage misyar in line with maqashid shari'ah at the level of dharuriyah, hajjiyah and tahsiniyah. The marriage misyar just to meet the biological needs, what can be said that this marriage is compatible with maqashid asy-syari'ah especially at the level of dharuriyah? At last it can be concluded marriage misyar irrelevant to maqashid asy-syari'ah padal level dharuriyah.